1952
DOI: 10.2118/952329-g
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Permeability With Overburden Pressure

Abstract: Oil bearing rocks, usually found at depths of 2,000 to 10,000'Ft, areelastically deformed by overburden pressure. Although the change in porositywith pressure in a number of example rocks has been shown to be small, it wasthought that overburden pressure might have a significant effect onpermeability. This note presents results of an investigation to determine themagnitude of the change in permeability with pressure. In routine core analysis, permeabilities are measured on rock samples whichare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
1

Year Published

1977
1977
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(79 citation statements)
references
References 0 publications
2
76
0
1
Order By: Relevance
“…Wyble (1958) performed similar experiments on three different sandstone samples to determine the changes in conductivity, porosity and permeability at pressure range 0 to 5,000 psig. His results were consistent with the observation by Fatt and Davis (1952). During the experiments, different overburden pressures (radial force) were applied only to the cylinder core while the axial direction was kept at constant atmospheric pressure.…”
Section: Effect Of Overburden Pressure On Unfractured and Fractured Psupporting
confidence: 90%
See 1 more Smart Citation
“…Wyble (1958) performed similar experiments on three different sandstone samples to determine the changes in conductivity, porosity and permeability at pressure range 0 to 5,000 psig. His results were consistent with the observation by Fatt and Davis (1952). During the experiments, different overburden pressures (radial force) were applied only to the cylinder core while the axial direction was kept at constant atmospheric pressure.…”
Section: Effect Of Overburden Pressure On Unfractured and Fractured Psupporting
confidence: 90%
“…The reduction in permeability with overburden pressure has been well known. Fatt and Davis (1952) presented the changes in permeability with pressure at range 0 to 15,000 psig and found that overburden pressure caused a reduction in permeability of the consolidated oil-bearing sandstone samples by as much as 50 per cent at 10,000 psig. Wyble (1958) performed similar experiments on three different sandstone samples to determine the changes in conductivity, porosity and permeability at pressure range 0 to 5,000 psig.…”
Section: Effect Of Overburden Pressure On Unfractured and Fractured Pmentioning
confidence: 99%
“…Stress sensitivity phenomena occur in the process of oil and gas field development of fractured reservoirs [13][14][15]39]. Natural fractures are the main fluid flow channels in tight sandstone and fractured carbonate reservoirs [40], which are the main factors in the development of oil and gas wells.…”
Section: Stress Sensitivity Experimentsmentioning
confidence: 99%
“…Permeability is well known to negatively correlate with the effective stress [13], and the stress-dependent permeability becomes the norm of petrophyiscal characterization for, but not limited to, fractured reservoirs [14,15]. Experimental studies on the stress-sensitivity reveal that fracture aperture is the reciprocal of the effective stress, and is one of…”
Section: Introductionmentioning
confidence: 99%
“…The natural compression of the material by the overburden weight results in an increase in density and decreasing porosity with increasing depth (Fatt, 1952;Bass, 1980). The increase in pressure due to taller leach columns also leads to a reduction in the porosity and, therefore, a decrease in leaching efficiency (Dixon, 2007).…”
mentioning
confidence: 99%